Does Higher EU Spending Lead to a Crowding-Out Effect on National Public Investments in the Environment Protection Sector? - Szymczak, Magdalena; Ochot, Artur (Czy zwiększenie funduszy strukturalnych powoduje efekt wypierania krajowych inwestycji w obszarze ochrony środowiska?, 2025)
Aim: An assessment of whether in the environmental protection sector, an increase in ESIF spending for a country results in a decrease in national spending and to identify countries where this is the case. Methodology: Annual data from Eurostat and Structural Funds databases were used. The values of ESIF and national expenditures transferred to environmental protection for the period 2007–2020 (the last two multiannual budget periods) to GDP and per capita were identified and compared with linear regression models between EU and national spending. A group of countries with the largest increase in ESIF expenditure in the study area was selected, and an analysis of national expenditure trend models was carried out for them. Results: No crowding-out effect of increased ESIF spending on environmental investment at the national level was found. Countries with a downward trend in national environmental expenditure were also identified: Cyprus, Lithuania and, in one dimension, also Poland. This indicates that these countries are ceding competence in environmental funding to the EU. Implications and recommendations: Giving out the financial sovereignty of the environment protection sector to the EU may trigger non-desirable social trends to act against sustainable development. For EU countries it would be better to pursue ecological policies convergent with international needs. Originality/value: The topic is relevant given the vast increase in the EU’s commitment to the environment and sustainable development in each successive multiannual budgetary perspective.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 1, s. 32-45
Keywords: ESIF; environment protection; public spending; environmental subsidy; ochrona środowiska; wydatki publiczne; dotacje na ochronę środowiska